UNCTAD Handbook of Statistics 2017 - United Nations Conference on Trade; Development (United Nations, 2017)
The UNCTAD Handbook of Statistics was first launched in 1967. Over the past 50 years, the handbook has evolved to incorporate new statistics and ensure that readers have access to the best possible information available. The 2017 edition of the Handbook continues in this tradition of excellence and innovation. On the 50th anniversary of the first UNCTAD Handbook of Statistics, we are proud to launch our new and updated version. This new presentation style is designed to integrate the detailed and lengthy statistical time-series available on our UNCTADstat data center with summary tables, state-of-the-art charts, maps and modern infographics.